DAMPAK KEGIATAN SEKOLAH PASAR TERHADAP PELAKU PASAR (Studi Kasus Pada Program Manajemen Pemberdayaan Pasar Rakyat di 50 Kabupaten/ Kota Tahun 2015) - Setiana, Mida (Istek Widuri Jakarta, 2017)
This study adopts Market School activities that have been done by volunteers of Gajah Mada University in Yogyakarta, on a case study of traditional market empowerment program in 50 districts / cities by 2015. The research has three objectives, namely: (1) to introduce participatory models, (2) to increase knowledge and capacity of trader, and (3) to achieve the impact of Market School. In order to achieve those objectives, the researcher uses the method of action research, specifically Participatory Action Research.This research result shows us that the Market Facilitator has played the role in simplifying the process though some methods of data/issues collection such as in-depth interview, brainstorming and problems prioritizing. In terms of education, Adult Learning Method (ALM) with popular way and attractive package really energized the member of Market School to join actively. The same good process was also noticed from the result of issues collection. Both observation data and issue priority show that physical related problems are the biggest issue, followed by issues related to trader and other problems related to marketing management. This condition indirectly explains that the revitalization on the physical aspects in market bringing significant impact on revitalization for the other aspects.Anyway the impact of the Market School are: (1) The use of various data collection techniques were responded positively by market player, (2) Participants in Market School get new necessary insight and skill that they never get before, such as simple accounting, how to set layout and arrange the goods, marketing management, accessing the capital, and how to run more updated business model such as online business,(3) The relationship between trader and management is getting better and more communicative, and (4) Building a sense of belonging from the trader to the market increases.